Genes & DNA - Charlotte K Omoto (Overseas Press ( India ) Private Limited, 2006)
Covers various aspects of contemporary biology including gene therapy, the Human Genome Project, DNA testing, and genetic engineering, and fundamental concepts. This book discusses classical and molecular genetics, quantitative and population genetics including cloning and genetic diseases, and the many applications of genetics to the world.